Probiotics for the management of kidney stone disease - Lewanika, Thokozile R (Division of Cell Biology, 2023)
Kidney stones contain various combinations of chemicals, however, 80% consist of calcium oxalate. Oxalate in humans is either absorbed into the urinary tract and excreted in urine or degraded by gut bacteria. Oxalate-degrading gut bacteria play a critical role in human oxalate homeostasis, evidenced by increased research interest in them as potential probiotics in the management of kidney stone disease. In South Africa, kidney stones are more prevalent in the white than in the black population, despite the latter having a diet that puts them at greater risk of developing kidney stones. It was, therefore, postulated in this study that differences in oxalate-degrading bacteria contributes to the observed South African kidney stone statistics. The major aims of this study were, consequently, to investigate the faecal micro biota of black and white South Africans, with respect to oxalate-degrading bacteria; and to identify and characterise novel oxalate-degrading probiotic candidates. The study population comprised twenty stone-free black and white South African males on a normal diet. Results obtained using PCR detection and denaturing gradient gel electrophoresis (DOGE) analyses showed differences in the oxalate-degrading bacteria between the two populations, with the black population recording a higher incidence of known oxalate-degrading bacterial species (70%) vs. the 30% recorded in the white population. Furthermore, culturable faecal bacteria isolated from the black population had greater oxalate-degrading capacities than those isolated from their white counterparts. Oxalate-degrading gut bacteria could, therefore, contribute to the lower incidence of kidney stones in the black South African population, relative to the white one. Two novel oxalatedegrading Escherichia coli and Clostridium innocuum strains were isolated from the faecal microbiota of a black test subject and physiologically characterised. Both species grew in oxalate-enriched media and the E. coli isolate degraded oxalate under both aerobic and anaerobic conditions. In silico genome screening of Lactobacillus genomes identified an oxalate-degrading strain of Lactobacil/us gasseri. Its oxalate-degrading mechanism was physiologically and transcriptionally characterised using in vitro growth studies coupled with RNA hybridisation analyses and reverse transcriptase PCR. In addition, the bacterium had significant oxalate-degrading ability under simulated in situ conditions in a continuous culture simulator of the human colonic microbiota. This bacterium is a viable candidate for use in the therapeutic management of kidney stone disease.